A petition to kill: Efficacious arzees against big cats in India - Mathur, N (Cambridge University Press, 2019)
In a political culture that experiences inordinately high levels of petitioning, what makes for a successful petition? This article studies petitions that have been efficacious in their appeals to capture or kill big cats in Himalayan India. The rates of success for any appeal against big cats are low in contemporary India, given the stringent legal regime that is geared almost exclusively towards the protection of the charismatic and endangered big cats as well as the hegemonic position occupied by wildlife conservationism. Furthermore, not only is it difficult to petition against cossetted big cats, but it is also not an easy task for any petition to be heard and acquiesced to. Through an ethnography of efficacious petitions, this article makes three related interventions. First, and in the process of attending to the rarity of a handful of efficacious petitions, this article argues for expanding our conceptualization of what, in practice, a petition is. It does so by outlining the changing forms of efficacious petitions, which can range from a telephone call, a register entry, a WhatsApp message from a smart phone, to the more ‘traditional’ paper-based petition. Beyond its ever-evolving medium, this article demonstrates the criticality of folding petitioning into a wider process that involves planning, performance, perseverance, repetition, and the capacity to elicit visceral responses. Finally, through an ethnographic foregrounding of human-big cat interactions, it demonstrates how an acceptance and elaboration of animal agency enriches the study of politico-legal processes.